2011
DOI: 10.1021/ja2083152
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Decomposition of the Human Defense Factor Hypothiocyanite Near Physiological pH

Abstract: Relatively little is known about the reaction chemistry of the human defense factor hypothiocyanite (OSCN(-)) and its conjugate acid hypothiocyanous acid (HOSCN), in part because of their instability in aqueous solutions. Herein we report that HOSCN/OSCN(-) can engage in a cascade of pH- and concentration-dependent comproportionation, disproportionation, and hydrolysis reactions that control its stability in water. On the basis of reaction kinetic, spectroscopic, and chromatographic methods, a detailed mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 48 publications
0
23
0
4
Order By: Relevance
“…In this pathway, IRF3 is activated by the linear ubiquitination of its lysine residues, which triggers its interaction with B-cell lymphoma 2-associated X protein (BAX), leading to mitochondrial activation and apoptosis (Chattopadhyay et al 2016). It has been reported that lysine residues can be carbamylated with cyanate (Wang et al 2007), a decomposition product of HOSCN (Kalmár et al 2011). Therefore, it is possible that HOSCN inhibits the interaction of IRF3 with BAX by blocking the ubiquitination of IRF3 lysine residues.…”
Section: Discussionmentioning
confidence: 99%
“…In this pathway, IRF3 is activated by the linear ubiquitination of its lysine residues, which triggers its interaction with B-cell lymphoma 2-associated X protein (BAX), leading to mitochondrial activation and apoptosis (Chattopadhyay et al 2016). It has been reported that lysine residues can be carbamylated with cyanate (Wang et al 2007), a decomposition product of HOSCN (Kalmár et al 2011). Therefore, it is possible that HOSCN inhibits the interaction of IRF3 with BAX by blocking the ubiquitination of IRF3 lysine residues.…”
Section: Discussionmentioning
confidence: 99%
“…(SCN) 2 is produced through comproportionation reactions of HOSCN and SCN À [5]. Above pH 2, the comproportionation reaction is slow and intermediate (SCN) 2 reacts rapidly with HOSCN to give disproportionation products [38]. When the pH is above 2, based upon previous kinetic studies, we would expect the transient concentration of (SCN) 2 to be low, and (SCN) 2 would be too unstable (for example with respect to its reaction with HOSCN) to participate in Trp oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…79,94,95 SPO je strukturno i katalitički slična laktoperoksidazi. 96 74,100 HOSCN je moćno mikrobicidno sredstvo koje ubija ili sprječava rast patogena: 70,79,80,85,86,101,102 raznih bakterija (uključujući i Heliobacter pylori), virusa koji se prenose oralnim putem (herpes simplex 1, respiratorni sincicijski virus, echovirus tip 11, HIV), nekih gljivica (primjerice, Candida albicans) i parazita (npr. Toxoplasma gondii).…”
Section: Ključne Riječiunclassified